TECHNOLOGICAL PROCESS OF OBTAING СOLD HARDENING MIXTURES (CHM) ON THE BASIS OF OLIGOFURFURILOKSISILAKSANOV BINDINGS - O. I. Ponomarenko; N. S. Evtushenko (Литьë и металлургия)
The research of environmentally friendly pitches based on the oligo-furfuriloksisilaksanovykh bindings with acid catalysts for the cold hardening mixtures to receive high-quality castings in foundry shops of plants is given in the article. Research was conducted by standard techniques on durability, survivability, permeability to gases, friability, adherence, peeling and metal penetration. Mathematical models of properties of mixture are developed and optimization of composition of mixture is made. Researches of change of properties of mixtures of the waste sand are conducted.